POLA ASUH ANAK MENURUT CHANAKYA NITI SHASTRA - Kusuma Dewi, Ni Wayan Sri Prabawati (Institut Hindu Dharma Negeri Denpasar, 2019)
The increasing number of cases of violence that have occurred in the community lately, have been carried out by children to other, making parents worried. They feel that the environment in which their children are growing is no longer conducive. Furthermore, parents are convinced that most children today need appropriate help and treatment. There are three trends of parenting applied by parents to their children, namely: authoritarian, permissive and democratic parenting. These three patterns are influenced by the factors of maturity, education and diversity of parents. Caregiving cannot be separated from the understanding that every child experiences a sensorimotor, pre-operational, concrete operational and formal operational phase throughout their lifetime. This work describes descriptively about parenting as taught and inspired by Maharsi Chanakya in his work Niti Sastra. He said that it is better to have one suputra child, than one hundred kuputra children, and a suputra child who brings glory to his family. For this reason, parenting when children aged zero to five years should be spoiled, when children aged six to fifteen can be cared for by punishments, and when children are sixteen years and over, children can be educated by means of friendship.